A companion to Luis de Molina - Kaufmann, Matthias, 1955- (Brill's companions to the Christian tradition, 2013)
Focused on Molina's main works the book offers the first comprehensive synopsis of his partly revolutionary philosophical positions concerning metaphysics of freedom, political philosophy, theory of law and their historical and systematic influence from the 17th century until today.